Curing characterization of pressureless sintered die attach material as leadfree salution in microelectronics packaging / Low Pui Leng - Low, Pui Leng (2019)
Tin-silver solder alloy is widely accepted as Pb-free alternative in power electronics. However, this solder alloy cannot meet the requirements of next generation industrial and automotive power drive systems. With the ever-increasing demand for wide bandgap semiconductors with junction temperature exceeding 165°C, the need to develop an alternative solution to traditional Tin-silver solders is unavoidable. Traditional tin-silver solders are unable to withstand the relatively high device operating conditions because of their lower melting temperature ~220°C. Silver sintering is a preferred material for high temperature packaging applications because it is substantially cheaper than gold and palladium but is not susceptible to the oxidation problems like other metals. It has significantly better electrical and thermal conductivity and is more reliable than traditional solder during temperature cycling. Its melting point is more than sufficient to withstand the high operating condition of wide bandgap devices. In this paper, pressureless silver sintering (Ag sintering) is presented as an alternative die-attach solution to traditional SnAg solder alloy. Unlike traditional solder, pressureless Ag sintering needs precise characterization of heat and temperature to achieve efficient solid-state bonding. Challenges in defining the optimum processing parameter such as, temperature, time and curing atmosphere will be enumerated in details. The objective of this work is to enhance the package performance of DRMOS package, housing one IC die and two FET dies. Macdermid Ag sintering paste D800HT2V was used in this study. Techniques such as thermogravimetric analyzer (TGA), differential scanning calorimeter (DSC), scanning electron microscope (SEM), and X-ray are also used to proliferate sintering efficiency. In parallel, electrical response between assembled devices curing under different environment will be conducted using Eagle Tester System 364.